Skills Profile: Exploring Skill Gaps in Aerospace within Industry 4.0. - Farinha, C.; Duarte, A.P.; Rosa, M. (SPACEMINHO, 2024)
The aerospace industry is characterized by a highly skilled and constantly changing workforce (Soares & Pinto, 2013). Therefore, cultivating a skilled and competent workforce capable of surmounting multifaceted challenges and seizing emerging opportunities is pivotal (Marrivada, 2022). Knowledge is the organization's primary source of economic advantage, and its significance is growing daily by making profes sionals who possess essential organizational expertise fundamental to companies (Barzinpour, et al. 2015). New technologies (e.g. Internet of things, artificial intelligence/machine learning, industry 4.0 and 5.0) are transforming the labour market, making it digitally qualified (Kar, et al., 2020). More specifically, the aerospace sector has experienced extensive changes that have consequently led to transformations in human resource management (HR) (d’Armagnac, et al., 2021). The skills and competences re quired to successfully overcome these challenges have not been the object of a thorough analysis. Thus, it is essential to investigate what competencies and skills are needed by professionals, what types of rofessional profiles are in demand on the aerosp ace industry (Research question 1). We expect to answer this question by firstly identifying the gaps between what educational institutions/professionals are offering, and which profiles and skills these industries are searching for. It is anticipated that this will aid in a more thorough examination of this issue and, inadvertently, to assist in reformulating skill based instruction to put a greater emphasis on professional development. Complementary, we want to investigate the academic background these pr ofessionals have acquired. (Research question 2). This question allows us to deepen in this way, the areas of professional training and degrees of aerospace area, skills and possible emerging professional fields, types of requalification and strategies tha t these professionals had to turn to adapt and anticipate changes, with a focus on reskilling/upskilling and lifelong learning. Moreover, it is also intended to explore what are the young adults'/students’ perceptions of these industries, highlighting the technological developments that the market is currently experiencing (Research question 3). There is a need to explore how to attract more young people to these industries, the role of environmental sustainability and work life balance in this area. The pr esent project will result in the creation of a competency model, which structures and defines technical and transversal competencies, serving as a contribution to HR managers to empower professionals in industries. However, it is uncertain how this can be implemented in practice (Research question 4). By piloting an intervention based in insights from the work conducted in the framework of questions 1 3, it contributes to an instrument that can be used for a better adaptation of competencies, considering th e constant need to renew these capabilities through reskilling and upskilling processes. Addressing the evolving demands of the aerospace industry requires a multifaceted approach encompassing education, training, and professional development initiatives i n order to cultivate talent pipelines, facilitate knowledge transfer, and promote diversity and inclusivity within the workforce. Moreover, competency frameworks aid the development of reskilling and upskilling programs that are essential to empower profes sionals to adapt to technological disruptions and seize emerging opportunities.